In search of rare variants: Preliminary results from whole genome sequencing of 1, 325 individuals with psychophysiological endophenotypes. (December 2014) - Vrieze, Scott I.; Malone, Stephen M.; Vaidyanathan, Uma; Kwong, Alan; Kang, Hyun Min; Zhan, Xiaowei; Flickinger, Matthew; Irons, Daniel; Jun, Goo; Locke, Adam E.; Pistis, Giorgio; Porcu, Eleonora; et al.
Abstract Whole genome sequencing was completed on 1, 325 individuals from 602 families, identifying 27 million autosomal variants. Genetic association tests were conducted for those individuals who had been assessed for one or more of 17 endophenotypes (N range = 802–1, 185). No significant associations were found. These 27 million variants were then imputed into the full sample of individuals with psychophysiological data (N range = 3, 088–4, 469) and again tested for associations with the 17 endophenotypes. No association was significant. Using a gene‐based variable threshold burden test of nonsynonymous variants, we obtained five significant associations. These findings are preliminary and call for additional analysis of this rich sample. We argue that larger samples, alternative study designs, and additional bioinformatics approaches will be necessary to discover associations between these endophenotypes and genomic variation.